An unexpected host for the endangered Giant Freshwater Pearl Mussel Margaritifera auricularia (Spengler, 1793) as a conservation tool - Soler, Joaquín; Boisneau, Catherine; Jugé, Philippe; Richard, Nina; Guerez, Yann; Morisseau, Laure; Wantzen, K. M.; Araujo, Rafael (Aquatic Conservation: Marine and Freshwater Ecosystems, 2019)
The giant freshwater pearl mussel Margaritifera auricularia (GFPM) is one of the most endangered bivalve species in the world. Originally occurring in many European rivers, the GFPM is a relict now restricted to a few ageing populations in France and Spain in which natural reproduction is almost absent. Like most unionoid mussels, the GFPM needs host fish for the development of their parasitic larvae (glochidia). The European sturgeon (Acipenser sturio), the only known native host fish of the GFPM in France, is essentially extinct. Therefore, the aim of this study was to identify other hosts that could be responsible for the few cases of recent recruitment. Natural infestation of wild fishes in three French rivers was assessed to identify potential hosts of M. auricularia, while artificial infestation experiments were conducted on the sea lamprey (Petromyzon marinus) and the wels catfish (Silurus glanis) to determine their compatibility as hosts. Among the 29 fish species assessed for natural infestation, only the three-spined stickleback (Gasterosteus aculeatus) and the European eel (Anguilla anguilla) carried M. auricularia glochidia. In the artificial infestation experiments, living juvenile mussels were collected from both P. marinus and S. glanis. The number of juveniles collected from a single P. marinus specimen (13,827) suggests that this species is a highly efficient host. As with previously known hosts, newly identified ones also appear to have a relationship with marine environments. The present findings suggest that P. marinus has played a key role in preventing the total extinction of M. auricularia in France, and indicate the potential use of P. marinus in conservation strategies aimed at reintroducing or stabilizing populations of this rare mollusc.